2015
DOI: 10.1503/jpn.120073
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: Altered affective, executive and sensorimotor resting state networks in patients with pediatric mania

Abstract: Brain blood flow and local synchrony abnormalities in medication-free patients with MDD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Abnormally increased amygdala activity may be more evident in youth than in adults with bipolar disorder(139). Studies in bipolar disorder youth also demonstrated abnormally decreased amygdala volumes(69,142,143); decreased orbitofrontal cortex and anterior cingulate cortex gray matter(142); abnormally reduced fractional anisotropy in white matter tracts connecting prefrontal and subcortical regions(144-147); and also in at-risk youth(148); and altered resting state in prefrontal cortical circuitry(149), and largescale networks(150). Longitudinal studies are clearly needed to examine developmental trajectories of structural and functional changes in prefrontal cortical-subcortical circuitry in individuals with bipolar disorder, and those youth at risk of future mood and psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormally increased amygdala activity may be more evident in youth than in adults with bipolar disorder(139). Studies in bipolar disorder youth also demonstrated abnormally decreased amygdala volumes(69,142,143); decreased orbitofrontal cortex and anterior cingulate cortex gray matter(142); abnormally reduced fractional anisotropy in white matter tracts connecting prefrontal and subcortical regions(144-147); and also in at-risk youth(148); and altered resting state in prefrontal cortical circuitry(149), and largescale networks(150). Longitudinal studies are clearly needed to examine developmental trajectories of structural and functional changes in prefrontal cortical-subcortical circuitry in individuals with bipolar disorder, and those youth at risk of future mood and psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies used a region of interest (ROI) analysis approach: one reported increased connectivity between the left DLPFC and superior temporal cortex in youth with BD relative to healthy youth, 19 and the other reported decreased amygdala-posterior insula connectivity in BD youth 20 . Using a model-free independent components analysis (ICA) approach, Wu et al 21 found that youth with BD exhibited altered affective, executive, and sensorimotor networks, and that greater connectivity of the right amygdala within the affective network was associated with better executive function in children with BD, but not in controls. Collectively, the results of these studies suggest that pediatric BD is characterized by aberrant patterns of prefrontal and limbic connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on fMRI findings in the amygdala obtained during rest in adults and youth with BD, 17,18,20,21 we predicted that, compared with healthy youth, youth with BP-I would exhibit disrupted functional connectivity at rest between amygdala subregions and key brain regions associated with emotion expression and emotion regulation, including the VLPFC, ACC, and insula. We also predicted that these aberrant patterns of connectivity in amygdala subregions would be associated with core symptom dimensions of BD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been corroborated in a sample of 36 children (ages 7-11), 17 of which had a history of MDD [42]. However, other studies found greater RSFC between sgACC and frontal regions in unmedicated adolescents with MDD (n=23) compared to controls (n=36) [43] and in adolescents/young adults with MDD (n=18) compared to controls (n=20) [44]. Furthermore, while Gaffrey and colleagues found greater RSFC between the sgACC and precuneus among their children with histories of MDD [42], Connolly et al found lower RSFC between sgACC and precuneus in their adolescent MDD group [43].…”
Section: Resting State Functional Connectivity Studies With Clinical mentioning
confidence: 74%
“…However, other studies found greater RSFC between sgACC and frontal regions in unmedicated adolescents with MDD (n=23) compared to controls (n=36) [43] and in adolescents/young adults with MDD (n=18) compared to controls (n=20) [44]. Furthermore, while Gaffrey and colleagues found greater RSFC between the sgACC and precuneus among their children with histories of MDD [42], Connolly et al found lower RSFC between sgACC and precuneus in their adolescent MDD group [43]. Divergence of findings in the pattern of sgACC RSFC abnormalities across studies may stem from differences in methodological steps, sample characteristics (e.g.…”
Section: Resting State Functional Connectivity Studies With Clinical mentioning
confidence: 94%